Sistem Informasi Perencanaan Aplikasi Penjualan Buku Online Berbasis Android - Rizki Nanda Winata Prasetya; Muhammad Sukron; Rizki Hidayat Pane; Muhammad Hafiz Al Fazri; Muhammad Alda (Forum Kerjasama Pendidikan Tinggi (FKPT), 2025)
The rapid development of the internet encourages people to live more practically and easily. Previously, the internet could only be enjoyed by certain people and its functions were limited. The internet currently greatly supports activities in all areas of life, for example, business and trade. At this time, business entities, both large companies, organizations and individuals have utilized the internet for their business, for example, business and trade in the food sector online. The popular term in the world of business and online trade is e-commerce. The Android application created by the author is a design for an online book sales system that uses e-commerce. This e-commerce book sales application is designed to make it easier for prospective buyers to make purchases and transactions through mobile devices and the internet. In addition, this application can save time and energy for prospective buyers. The process of this application was developed using the Rapid Application Development (RAD) method, which focuses on accelerating development through prototype literacy and direct user feedback. The main features offered by this application include book catalog management, ordering system, registration system, book upload system to be sold which is easily accessed via computer and mobile devices. The RAD method is the method used in designing this application, because RAD allows application development to be carried out more efficiently with user involvement from the early stages, ensuring that their needs can be met appropriately.